STRATEGI PENGEMBANGAN USAHA AGROINDUSTRI KOPI LUWAK SEBAGAI ATRAKSI WISATA PADA AGROWISATA DI KABUPATEN TABANAN - Decky Yodharya, Putu; Satriawan, I Ketut; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2013)
This study aims to know the types of agro-tourism can be an attraction in and formulate appropriate strategies for development. In this study there are several steps that are used starting agroindustry identification, collection and sampling, identification places agro-industry, External & Internal Environment Analysis, Strategy formulation using SWOT and final selection of alternative strategies using QSPM The results showed that the analysis of internal factors and external objects have been surveyed from the two sampled agro-tourism obtained IFE total weighted scores for 2,769 and 2,874 by placing second EFE agro-tourism that the cells in the matrix V IE. These positions describe both agro tourism can implement defense strategies. Priority selection strategy by using QSPM, recommending business development strategy based on six strategy alternatives derived from the SWOT matrix and matrix IE put alternative strategy Working with investors or with relevant government agencies to maximize the quality and quantity of agro products and agro-industry development opportunities in Denpasar to Bedugul tourist track on the top spot with a total score of weight 5,719 Keywords: agro-tourism, agro-industry, strategy, tourist atractions. PENDAHULUAN
Keywords: 10